Improvement of UP Diliman public transport network model using Cube - Eden, Mel Francis S.; Saquing, Frances Sarah A.; Vergel, Karl B. N.; Orozco, Ivan Francis L. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The study's main objective is to initiate the development of the UP Diliman Public Transport Network Model by improving the existing public transport network model developed by the National Center for Transportation Studies for the pre-feasibility study of the AGT system using Cube Transport Modeling Software by Citilabs. The current approach of transport planners in improving the network is through trial-and-error modification of the network or by extensive feasibility studies which is unsustainable for a continously growing transport network. Macroscopic models are useful for assessing alternative scenarios on a transport network forecasted from the base scenario with minimal maintenance. The road network of the study are was created using geospatial data as a template and the transit lines were overlaid accordingly. Submodels were developed for route enumeration, route evaluation, and trip assignment as applications in the software. The model, and its parameters, were initially calibrated through empirical realism testing. The network resolution was increased by three times compared to the existing model. The model was also optimized for calibration for further development by minimizing the route bundles skimmed. Alternatives scenarios were developed and run for capability testing. It is recommended that the origin-destination matrix be updated before further calibration and any calibration performed thereon be based on additional studies and data collection.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Transportation -- University of the Philippines; Transportation -- Mathematical models